2016
DOI: 10.1200/jco.2015.63.2463
|View full text |Cite
|
Sign up to set email alerts
|

Financial Concerns About Participation in Clinical Trials Among Patients With Cancer

Abstract: Purpose The decision to enroll in a clinical trial is complex given the uncertain risks and benefits of new approaches. Many patients also have financial concerns. We sought to characterize the association between financial concerns and the quality of decision making about clinical trials. Methods We conducted a secondary data analysis of a randomized trial of a Web-based educational tool (Preparatory Education About Clinical Trials) designed to improve the preparation of patients with cancer for making decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
(1 reference statement)
1
30
1
Order By: Relevance
“…Minorities are more likely to be underinsured, to seek care at under-resourced hospitals, and to have concerns about the cost of participating in a clinical trial. 29,34 In addition, lack of or inadequate health insurance acts as a barrier to enrollment in clinical trials for several under-represented populations, including racial and ethnic minorities. 29,35 …”
Section: System-level Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Minorities are more likely to be underinsured, to seek care at under-resourced hospitals, and to have concerns about the cost of participating in a clinical trial. 29,34 In addition, lack of or inadequate health insurance acts as a barrier to enrollment in clinical trials for several under-represented populations, including racial and ethnic minorities. 29,35 …”
Section: System-level Barriersmentioning
confidence: 99%
“…33 Similarly, the health care system can also influence patient concerns about the cost of participating in trials and, in turn, their decisions to enroll or not enroll in a clinical trial. 34 Thus, these 2 levels are linked in terms of whether and how health care professionals and minority patients discuss clinical trials and whether minority patients agree to enroll.…”
Section: Individual-level Barriersmentioning
confidence: 99%
“…If a patient's distress is left unaddressed, it can lead to impaired decision making and poor care selfmanagement. [3][4][5] The rising costs of cancer treatment are increasingly shifted to the patient, which can contribute to financial distress. 6,7 One study found that patients with cancer who experienced unexpected medical costs had increased anxiety and depression and worse quality-of-life (QOL) outcomes over time.…”
Section: And the American College Of Surgeons Commission Onmentioning
confidence: 99%
“…This is particularly important because concerns about treatment-related cost may impact a patient’s ability to make high-quality treatment decisions, such as whether to enroll in a clinical trial [25]. Providers need to be able to guide patients regarding the risks and benefits (including financial toxicity) of alternative treatment options to help them choose treatments that reflect their preferences and values.…”
mentioning
confidence: 99%